2000
DOI: 10.1074/jbc.c000184200
|View full text |Cite
|
Sign up to set email alerts
|

Chitin-binding Proteins in Invertebrates and Plants Comprise a Common Chitin-binding Structural Motif

Abstract: Tachycitin, a 73-residue polypeptide having antimicrobial activity is present in the hemocyte of horseshoe crab (Tachypleus tridentatus). The first three-dimensional structure of invertebrate chitin-binding protein was determined for tachycitin using two-dimensional nuclear magnetic resonance spectroscopy. The measurements indicate that the structure of tachycitin is largely divided into N-and C-terminal domains; the former comprises a three-stranded ␤-sheet and the latter a two-stranded ␤-sheet following a sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(122 citation statements)
references
References 29 publications
5
116
0
1
Order By: Relevance
“…The fold comprises predominantly coil, but does have two small β-sheets and a small region of helix ( Figure 1). This fold can accommodate a surprisingly extended binding site as exemplified by WGA, [52]); (e) family 2 CBM, Cf CBM2, from Cellulomonas fimi (PDB code 1EXG [81]); (f) family 9 CBM, TmCBM9-2, from T. maritima in complex with cellobiose (PDB code 1I82 [33]); (g) family 32 CBM, MvCBM32, from Micromonospora viridifaciens in complex with galactose (PDB code 1EUU [65]); (h) family 5 CBM, EcCBM5, from Erwinia chrysanthemi (PDB code 1AIW [82]); (i) family 13 CBM, SlCBM13, from S. lividans in complex with xylopentaose (PDB code 1MC9 [48]); (j) family 1 CBM, TrCBM1, from Trichoderma reesi (PDB code 1CBH [83]); (k) family 10 CBM, CjCBM10, from Cellvibrio japonicus (PDB code 1E8R [84]); (l) family 18 CBM from Urtica dioca in complex with chitotriose (PDB code 1EN2 [85]); (m) family 14 CBM, tachychitin, from Tachypleus tridentatus (PDB code 1DQC [86]). Bound ligands are shown as 'liquorice' representations, while bound metal ions are shown as a blue spheres.…”
Section: Hevein Foldmentioning
confidence: 99%
“…The fold comprises predominantly coil, but does have two small β-sheets and a small region of helix ( Figure 1). This fold can accommodate a surprisingly extended binding site as exemplified by WGA, [52]); (e) family 2 CBM, Cf CBM2, from Cellulomonas fimi (PDB code 1EXG [81]); (f) family 9 CBM, TmCBM9-2, from T. maritima in complex with cellobiose (PDB code 1I82 [33]); (g) family 32 CBM, MvCBM32, from Micromonospora viridifaciens in complex with galactose (PDB code 1EUU [65]); (h) family 5 CBM, EcCBM5, from Erwinia chrysanthemi (PDB code 1AIW [82]); (i) family 13 CBM, SlCBM13, from S. lividans in complex with xylopentaose (PDB code 1MC9 [48]); (j) family 1 CBM, TrCBM1, from Trichoderma reesi (PDB code 1CBH [83]); (k) family 10 CBM, CjCBM10, from Cellvibrio japonicus (PDB code 1E8R [84]); (l) family 18 CBM from Urtica dioca in complex with chitotriose (PDB code 1EN2 [85]); (m) family 14 CBM, tachychitin, from Tachypleus tridentatus (PDB code 1DQC [86]). Bound ligands are shown as 'liquorice' representations, while bound metal ions are shown as a blue spheres.…”
Section: Hevein Foldmentioning
confidence: 99%
“…This blue shift indicates that one of the Trp residues becomes more solvent-buried upon complexation, which is most likely Trp 71 because the corresponding residue in Tachycitin is solvent-exposed (9). In contrast, Trp 63 would remain solvent-buried because Trp 63 is involved in a hydrophobic interaction in the core of the protein with Tyr 38 (again based on the structure of Tachycitin) (9). This hydrophobic interaction is strictly conserved based on the high degree of conservation of both aromatic residues in the CBM14 family.…”
Section: Table IImentioning
confidence: 99%
“…However, CBM18 is only fused to the plant-specific family 19 catalytic domain, whereas chitinases of mammals and invertebrates utilize CBM14 in combination with the family 18 catalytic domain. Sequence homology is missing between the two motifs, but the three-dimensional structure of Tachycitin revealed that CBM14 and CBM18 partially share their tertiary structure (9).…”
mentioning
confidence: 99%
“…4A). It is important to note that Rtv does not contain any known chitin binding do-main or any other motif found in cuticle proteins (Andersen et al, 1995;Shen and Jacobs-Lorena, 1999;Suetake et al, 2000Suetake et al, , 2002 and, therefore, defines a new class of cuticle proteins.…”
Section: Rtv Is Homologous To a Diverse Superfamily Of Extracellular mentioning
confidence: 99%
“…However, an instructive role for fiber orientation is assigned to the so-called plaques at the apical plasma membrane that are thought to harbor enzymes required for chitin synthesis (Locke, 1976). On the molecular level, it has been proposed that ␤-sheet conformation in the conserved domains of cuticular proteins such as the R&R chitin binding motif and the tachycitin-like chitin binding domain may be crucial for chitin binding (Suetake et al, 2000;Rebers and Willis, 2001;Hamodrakas et al, 2002;Togawa et al, 2004) and that this association may be responsible for the characteristic organization of the laminae (Fraenkel and Rudall, 1947;Iconomidou et al, 1999). Commonly, aromatic amino acids have been demonstrated to be implicated in the interaction between chitin binding proteins and their substrate (Asensio et al, 1998;Rebers and Willis, 2001;Hardt and Laine, 2004;Katouno et al, 2004).…”
Section: Introductionmentioning
confidence: 99%